1988
DOI: 10.1111/j.1467-8624.1988.tb01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant Visual Attention in the Paired-Comparison Paradigm: Test-Retest and Attention-Performance Relations

Abstract: The visual behavior of infants in the paired-comparison paradigm was assessed with multiple discrimination tasks week-to-week at 4 and 7 months and longitudinally from 4 to 7 months. Results indicated that although task-to-task reliability was extremely variable and typically low, most measures of infants' attention averaged across multiple tasks were reliable from 1 week to the next as well as relatively stable over the longer longitudinal period. Across all groups, infants who had shorter fixations (i.e., mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 30 publications
10
57
1
Order By: Relevance
“…Furthermore, 6.5-month -olds allowed to accumulate 5 s of looking during familiarization with an object, subsequently demonstrated familiarity preferences in a VPC task; however, infants of the same age allowed to accumulate 15 s or longer of looking during familiarization demonstrated novelty preferences. These findings and others (e.g., Colombo, Mitchell, & Horowitz, 1988; Fagan, 1974; Freeseman, Colombo, & Coldren, 1993; Richards, 1997; Rose et al, 1982) demonstrate that longer familiarization leads to greater evidence of object recognition in infants; and with increasing age, infants require less exposure during familiarization to subsequently recognize an object. Additionally, Diamond (1990) found that with increasing age infants demonstrate evidence of recognition memory following longer delays between familiarization and testing.…”
Section: Preferential Looking Visual Attention and Recognition Memosupporting
confidence: 58%
“…Furthermore, 6.5-month -olds allowed to accumulate 5 s of looking during familiarization with an object, subsequently demonstrated familiarity preferences in a VPC task; however, infants of the same age allowed to accumulate 15 s or longer of looking during familiarization demonstrated novelty preferences. These findings and others (e.g., Colombo, Mitchell, & Horowitz, 1988; Fagan, 1974; Freeseman, Colombo, & Coldren, 1993; Richards, 1997; Rose et al, 1982) demonstrate that longer familiarization leads to greater evidence of object recognition in infants; and with increasing age, infants require less exposure during familiarization to subsequently recognize an object. Additionally, Diamond (1990) found that with increasing age infants demonstrate evidence of recognition memory following longer delays between familiarization and testing.…”
Section: Preferential Looking Visual Attention and Recognition Memosupporting
confidence: 58%
“…The preference may reflect infants’ ability to extract a global form. But it is also plausible that the preference instead reflects a simple preference for the illusory stimulus configuration over the non-illusory one (Colombo et al, 1988; Freeseman et al, 1993; Kavsek & Yonas, 2006), or detection of local configural or brightness differences that attract their attention (Bertenthal et al, 1980). Bulf and colleagues (2009) demonstrated that a Kanizsa figure embedded in a background of non-illusion-inducing pacmen elements did not guide the attention of 6-month-old infants, but infants nevertheless showed longer looking times for an isolated Kanizsa figure compared to a non-illusory organization of the same pacman elements.…”
Section: Discussionmentioning
confidence: 99%
“…Based on habituation and looking time methods, infants appear to perceive KIC figures, although researchers disagree as to the age at which this global perceptual ability is evident (range: 1 month to 8 months; Treiber & Wilcox, 1980; Bertenthal et al, 1980; Csibra, 2001; Otsuka et al, 2004; Bulf et al, 2009; Bremner et al, 2012). Some researchers have questioned whether the looking-time data actually indicate perception of the illusory shape or simply a novelty preference, a stimulus-related preference, or some other variable (Colombo et al, 1988; Freeseman et al, 1993; Kavsek & Yonas, 2006; Bulf et al, 2009; Sato et al, 2013), but other researchers argue that appropriate control conditions explicitly address potential confounding variables in static (Otsuka et al, 2008) and dynamic illusory displays (Curran et al, 1999; Kavsek & Yonas, 2006; Sato et al, 2013). Using a visual search paradigm combined with eye-tracking, Bulf and colleagues (2009) found that 6-month-olds did not attend to a KIC triangle when embedded in background noise, yet looked significantly longer at a KIC image compared with a non-illusory image.…”
Section: Local To Global Processingmentioning
confidence: 99%
“…Robust visual attention directed towards the eye region also appears to be indicative of holistic face processing [6263]. Human infants as early as 4–7 months of age likewise vary in how they distribute attention to face stimuli [64–65], and variation in attentional bias is associated with variation in face recognition. A large body of evidence indicates that infants who tend to process global properties before local properties, much as adults do, process information faster and more efficiently than infants who tend to focus initially on local aspects of the stimuli [6672].…”
Section: Discussionmentioning
confidence: 99%